Dual single-scission event analysis of constitutive transferrin receptor (TfR) endocytosis and ligand-triggered β2-adrenergic receptor (β2AR) or Mu-opioid receptor (MOR) endocytosis - Lampe, Marko; Pierre, Fabienne; Al-Sabah, Suleiman; Krasel, Cornelius; Merrifield, Christien J. (Molecular biology of the cell, 2014)
The dynamic relationship between constitutive and ligand-triggered clathrin-mediated endocytosis is only poorly characterized, and it remains controversial whether clathrin-coated pits specialize to internalize particular receptor cargo. Here we analyzed the ligand-triggered endocytosis of the model G-protein-coupled receptors (GPCRs) β2-adrenergic receptor (β2AR) and Mu-opioid receptor (MOR) at the level of individual endocytic events using a total internal reflection fluorescence microscopy (TIRFM)-based assay. Similar to the constitutive endocytosis of transferrin receptor (TfR), ligand- triggered endocytosis of β2AR occurs via quantized scission events hosted by clathrin spots and plaques of variable size and persistence. To address whether clathrin-coated structures (CCSs) specialize to internalize particular GPCRs, we adapted the TIRFM imaging assay to simultaneously quantify the internalization of TfR and the ligand- triggered endocytosis of the β2AR or MOR. Agonist-triggered β2AR or MOR endocytosis extended the maturation time of CCSs, as shown previously, but did not affect the rate of constitutive TfR endocytosis or loading of TfR into individual endocytic vesicles. Both the β2AR and the MOR receptors entered cells in the same vesicles as TfR, and the overall evidence for CCS specialization was weak. These data support a simple model in which different cargoes internalize through common CCSs.